Sodium brain trauma Prognostic value of the sodium alterations during the first seven days in adults patients with severe brain trauma of the autonomous institute university hospital of Los Andes Merida between June 2017 - June 2018 - DULCEY SARMIENTO, LUIS ANDRES (Technium: Romanian Journal of Applied Sciences and Technology, 2020)
Objectives To establish the prognostic role of serum sodium alterations during the first seven days in patients diagnosed with severe brain trauma admitted to the adult emergency area of ??the autonomous university hospital of the Mérida Andes, from June 2017 to June 2018 Materials and Methods: Prospective, field and longitudinal sectional study. Patients older than 18 years with a diagnosis of head brain injury were selected, diabetes insipidus, inappropriate antidiuretic secretion and salt loser brain were evaluated in each patient of the sample. Results: 103 patients, 90.6% men and 9.4% women, the mean age was 25.8 years, the largest age group corresponded to those under 30 years, 79 (76.9%), accidents of Transients were the main cause of brain trauma 79 (76%), brain edema was the main tomographic finding, all tomographic findings showed statistical significance. The 3 types of neuroendocrine disorders related to sodium were presented, being diabetes insipidus the most frequent. total mortality was 22 (22.63%) patients of 103. Neurosurgical interventions were performed in 10 patients with a mortality of 8 (80%), (p <0.001). The Glasgow score in the live group was 9.7 compared to 6.3 points in the deceased subgroup (p <0.001). Conclusions: There is a higher mortality associated with sodium alterations, the greatest association corresponded to diabetes insipidus (p0,026), so it is vital to adequately manage these alterations.